1264. Assessment of In Vivo Efficacy of CF-296 in addition to Vancomycin (VAN) and Daptomycin (DAP) against Staphylococcus aureus in the Neutropenic Murine Thigh Infection Model. (31st December 2020) - Asempa, Tomefa E; DeRosa, Nicole A; Cassino, Cara; Lehoux, Dario; Schuch, Raymond; Nicolau, David P
Abstract: Background: CF-296 is a novel lysin in pre-clinical development for the treatment of methicillin-susceptible and methicillin-resistant Staphylococcus aureus infections, used in addition to standard of care antibiotics including VAN and DAP. We evaluated the in vivo efficacy of CF-296 alone and in addition to VAN and DAP against S. aureus . Methods: Eight isolates (1 MSSA and 7 MRSA) were studied. Murine ICR MIC (100% serum) and human MIC (100% serum) for CF-296 ranged from 32-256 mg/L to 0.5-1 mg/L respectively. Broth microdilution MICs for DAP ranged from 0.5-1 mg/L while all isolates exhibited a VAN MIC of 1 mg/L. Neutropenic ICR mice were thigh inoculated with bacterial suspensions (10 7 CFU/mL). Mice were administered three monotherapy regimens subcutaneously (SC) or intravenously (IV): i) sub-therapeutic VAN, SC (i.e., a dose that yielded bacteria stasis or growth in order to evaluate further bacterial killing), ii) sub-therapeutic DAP, SC, or iii) CF-296 50 mg/kg, IV. Combination of sub-therapeutic VAN or DAP in addition to 5 escalating CF-296 doses ranging from 0.5 to 50 mg/kg were also examined. Control mice were vehicle-dosed. Efficacy was measured as the change in mean thigh bacterial density at 24h relative to 0h controls. Results: Relative to starting inoculum (5.71 ± 0.27 at 0h), bacterial density in controls increased by +2.49 ± 0.98 log10 CFU/thigh across all 8 strains. On average, VAN, DAP, and CF-296 monotherapy resulted in +0.90 ± 1.21, +1.47 ± 0.80, and +0.87 ± 1.39 log10 CFU/thigh bacteria growth, respectively. In addition to VAN, escalating CF-296 exposures (0.5 – 50 mg/kg) resulted in an augmented dose-response, ranging from bacterial reduction of -0.26 ± 1.10 (with addition of CF-296 0.5 mg/kg) to -1.01 ± 0.41 log10 CFU/thigh (with addition of CF-296 50 mg/kg). Similarly, escalating CF-296 exposures in addition to DAP resulted in an augmented dose-response, ranging from bacterial density of +0.80 ± 1.19 to -0.72 ± 0.59 log10 CFU/thigh. Conclusion: Compared with 24h control, VAN, DAP, and CF-296 alone displayed modest CFU reduction while CF-296 synergized with VAN and DAP to cause further bacterial killing highlighting a potential role for CF-296 adjunctive therapy against MSSA and MRSA isolates. Disclosures: Cara Cassino, MD, ContraFect Corporation (Employee)ContraFect Corporation (Employee) Dario Lehoux, PhD, ContraFect Corporation (Consultant) Raymond Schuch, PhD, ContraFect Corporation (Employee) David P. Nicolau, PharmD, Cepheid (Other Financial or Material Support, Consultant, speaker bureau member or has received research support.)Merck & Co., Inc. (Consultant, Grant/Research Support, Speaker's Bureau)Wockhardt (Grant/Research Support)